Pemberian Biskuit Tepung Ikan Teri (Stolephorus Commersonii) dan Tepung Daun Kelor (Moringaolefera) terhadap Peningkatan Kadar Volume ASI dan Berat Badan Ibu Nifas di Kota Palu - Arini Arini; Iin Octaviana Hutagaol (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2023)
The puerperium or puerperium period is the period after labor is completed up to 6 weeks or 42 days. During the puerperium, the reproductive organs will slowly experience changes as they were before pregnancy. This change in the reproductive organs is called involution. Based on the 2018 Riskesdas data, the process of starting breastfeeding mostly occurs 1-6 hours after birth (35.2%) and <1 hour (early breastfeeding initiation) at 34.5%. Meanwhile, the lowest breastfeeding initiation occurred at 7-23 hours after birth, which was 3.7%. It can be seen that the coverage of exclusive breastfeeding in 2020 decreased by 1.10% compared to coverage in 2019 (57.77%). Almost all Puskesmas in the Palu City area have exclusive breastfeeding coverage >50%, and refer to the 2020 Ministry of Health Strategic Plan target of 40%. This study aims to analyse the influence of biscuits and flour from flour anchovies kelor against the increasing volume of breastfeeding on the parturition.The specific objectives of this study were: 1) making biscuits from anchovy flour and Moringa flour, 2) Determining the serving size of biscuits per serving, 3) Analyzing the effect of giving biscuits from anchovy flour and Moringa flour to increase the volume of breast milk in postpartum mothers. The research design used a quasi-experimental one group pre and post-test. The used the test t pairs, One at the research is mother parturition Palu in some 20 mother parturition .The subject of study is population research which were selected purposively on inclusion and exclusion. This research result indicates that any impact of biscuits flour anchovies (stolephorus commersonii) and flour leaves kelor (moringaolefera) against weight mother parturition ( p 0,006 ) and volume breastfeeding worth (p 0,000 ).